FAKTOR-FAKTOR YANG MEMPENGARUHI SIKAP KONSUMEN TERHADAP IKLAN PRODUK DESSERT BOX DI INSTAGRAM SELAMA MASA PANDEMI COVID-19 - Indah Ria Lestari; Aryo Bismo; Antonia Monica Dharmaesti (Jurnal Bisnis Darmajaya, 2023)
The aim of this research is to analyze the effect of the perceived advertising value variable which is represented by the credibility, lack of irritation, informativeness, entertainment, and personalization variables on respondents' advertisement attitudes and their impact on respondents' brand attitudes. This research was conducted during the Covid-19 pandemic with 259 respondents who are residents of Jakarta and its surroundings through online questionnaires and the data obtained was processed using SEM-PLS. The results showed that all hypothesis testing in the study showed that credibility, lack of irritation, informativeness, entertainment, and personalization had a direct positive and significant effect on the advertisement attitudes and the brand attitudes. Advertisement attitudes has a positive and significant effect on the brand attitudes. Entrepreneurs and managers in the dessert box food industry can pay more attention to the perceived advertising value of Instagram ads by paying attention to informativeness, credibility, entertainment, lack of irritation, and personalization factors.